Isokinetic Training Effect of Ankle Positions on Knee Extensor Strength - Cha, Yong-Jun (The Society of Physical Therapy Science, 2014)
[Purpose] The purpose of this study was to determine which ankle position most influences knee extensor strength in training programs for strengthening the knee extensors using three different active ankle positions. [Subjects] Twenty-one healthy adults (6 males and 15 females) participated in this study. [Methods] Subjects were trained isokinetically in knee extension and flexion at 70 or 80% of 1RM under three actively and naturally fixed, contracted ankle conditions: dorsiflexion, plantarflexion, and resting position. After each group successfully executed the training four times a week for three weeks, mean peak torque (PT) and total work (TW) variables were measured and compared at 60°/sec and 180°/sec among the three groups. [Results] Significant differences were revealed in knee extensor TW at 60°/sec, PT and TW at 180°/sec, with the greatest PT and TW observed with the ankle in active dorsiflexion position. [Conclusion] These results suggest that active ankle dorsiflexion in a knee strength training program may be more effective at increasing knee extensor strength than a resting or plantarflexion position.